Acute acalculous cholecystitis as an early manifestation of COVID-19: case report and literature review. - D'Introno, Alessia; Gatti, Pietro; Manca, Giuseppe; D'Amuri, Alessandro; Minniti, Salvatore; Ciracì, Emanuela (Acta Biomedica Atenei Parmensis, 2022)
Background: The novel coronavirus disease 2019 (COVID-19) has rapidly spread worldwide since the outbreak in Wuhan, China, in 2019, becoming a major threat to public health. The most common symptoms are fever, dry cough, shortness of breath, but subjects with COVID-19 may also manifest gastrointestinal symptoms, and in a few cases an involvement of the gallbladder has been observed. Case report: Here we present a case of 50-year-old male with SARS-CoV-2 infection who had abdominal pain, vomiting and diarrhea without respiratory symptoms and was finally diagnosed as acute acalculous cholecystitis (AAC). Laparoscopic cholecystectomy was performed and found a gangrenous gallbladder; the real-time reverse transcription polymerase chain reaction SARS-CoV-2 nucleic acid assay of the bile was negative. We also made a review of the literature and try to understand the hypothetic role of SARS-CoV-2 in the pathogenesis of AAC. Conclusions: We highlighted that it is noteworthy to look at gastrointestinal symptoms in patients with SARS-CoV-2 infection and take into account AAC as a possible complication of COVID-19. Although more evidence is needed to better elucidate the role of the pathogenic mechanisms of the SARS-CoV-2 in AAC, it is conceivable that the hepatobiliary system could be a potential target of SARS-CoV-2.